Design and performance analysis of subcarrier multiplexing passive optical networks - Abdul Rashid, Hairul Azhar (2006)
Fiber-to-the-Home (FTTH) has been the main attraction in the telecommunication industry lately. Direct fiber connection has always been viewed as the long awaited solution due to the large bandwidth and low maintenance. However, in order for FTTH to remain competitive, a passive optical network is required. Subcarrier Multiplexing (SCM) is a potential solution for transmission in Passive Optical Networks (PON). In this study, three problems encountered in SCM PONs, namely Optical Beat Interference (OBI), Chromatic Dispersion (CD) and Cross Phase Modulation (XPM) are examined. Besides this, a performance analysis of an Optical Single Sideband (OSSB) SCM system influenced by phase and drive level error is alo carried out. A new extension to OSSB, an Optical Tandem Single Sideband (OTSSB) using Orthogonal Subcarriers is also proposed. Finally, a new CD and optical modulator chirp measurement technique using Four-Wave Mixing OBI (FWM-OBI) is proposed and optimized.